Are the playoffs different from the regular season? A comparison of in-game statistics in Icelandic elite handball - Laxdal, A.; Ivarsson, A.; Sigurgeirsson, O.; Haugen, T. (International Journal of Performance Analysis in Sport, 2023)
There are many axioms in sport that are taken at face value. One of them is that the playoffs are somehow totally different from the regular season. The aim of this study was to test that axiom by comparing in-game statistics during the regular season and the playoffs in the semi-professional Icelandic elite men`s handball league. Data from 724 games (648 regular season games and 76 playoff games; 1448 data points) across five seasons were analysed using a two-level logistic regression analysis. The variables of interest were pace, fast breaks, legal stops, penalty throws given, 2-minute suspensions, and saves. The results indicated no meaningful differences in fast breaks, penalty throws given or number of saves, but did find signs of added intensity during the playoffs with a higher pace, more legal stops and more 2-minute suspensions. While the differences were not particularly large, they have the possibility of being practically meaningful and were in line with the axiom. Possible explanations were discussed but more research is needed to determine whether these findings are context- or sport-specific.